HUBUNGAN PENGETAHUAN DAN SIKAP TERHADAP KEPATUHAN MINUM OBAT PASIEN TUBERKULOSIS PARU FASE LANJUTAN DI KECAMATAN UMBULSARI JEMBER - Elita Ismi Mientarini; Yohanes Sudarmanto; M Hasan (Fakultas Kesehatan Masyarakat, Universitas Jember, 2018)
Tuberkulosis (TB) is a infectious disease caused by t Mycobacterium Tuberculosis. Indonesia is the second country with highest number of TB cases in the world after India. Medication adherence is essential for successful TB treatment. One of the factors that can influence someone adherence to TB treatment is knowledge and attitude. This study aimed to know the correlation between knowledge and attitude towards the adherence of medication in tuberkulosis pulmonary patient on continuation phase in umbulsari jember. This study was an obsevational analytic using cross sectional with total sample technique method. Data were obtained through questionnaire (knowledge questionnaire, HRHS, and MMAS-8) then analyzed with Spearman correlation test (p= <0,05). The results showed a significant between compliance with knowledge at the level of know with the value of p = 0.041. While the results of the correlation of compliance with knowledge at the level of understanding and application and between attitudes and compliance obtained results not signifikan.